Microbial and biochemical activities in the rhizosphere of sandalwood - D.J. BAGYARAJ and C.K. SURESH, S. JAYANTHl, G. MAMATHA, (Indian Phytopathology, 2002)
An investigation was carried out with rhizosphere and nonrhizosphere soils collected from southern dry zone and transition zone of Karnataka. These soils were analysed for microbial population and enzyme activities. Red sandy loam is predominant soil type found in this zone. The microbial population was highest in grass rhizosphere in the transition zone where as it was on par with sandal rhizosphere in the southern dry zone. Bacterial population was more in sandal rhizosphere, which was on par with grass rhizosphere. Per cent mycorrhizal colonization was highest in sandal rhizosphere. However, there were two cases where the per cent colonization in grasses was on par with sandal. Mycorrhizal spore population was more in sandal rhizosphere and least in non-rhizosphere region. The alkaline phosphatase activity followed the same trend in case of southern dry zone soil whereas in case of transition zone this activity of rhizosphere soil of grass was more or less similar.